Principles and practice of veterinary technology
Now in full color, Principles and Practice of Veterinary Technology provides comprehensive coverage of the competencies every vet tech needs to know. Illustrated, step-by-step instructions emphasize the technician's role and responsibilities in each procedure, and dozens of new summary tables and boxes make it easy to find key information. Written by experienced vet tech educator Margi Sirois, this edition offers excellent preparation for clinical practice and for veterinary technician credentialing examinations